Pentadbiran harta pusaka GSA dalam sistem pentadbiran tanah negara dan bagi tanah felda - Mohd. Yusuf, Mohd. Yassin (2010)
Every human life will certainly die. That was the end of human life in this world. When a person dies funeral business has been completed, the responsibility of the heirs to settle the inheritance with the deceased prior settle debts, fulfill his will, if any, and finally dividing the property to the heirs entitled to inherit. The same happened to the community FELDA death. However, FELDA land has its own uniqueness that can not be held more than two people and can not be subdivided. In the event of death and the deceased left heirs of many, the name of the heirs can not all be registered in the title and this situation is not different from the land was gazetted in 1960 under the GSA. Therefore, a study carried out in FELDA Region Raja Alias, Negeri Sembilan which FELDA Raja Alias One, Felda Raja Alias four, FELDA troughs four and FELDA troughs 5 to see a small estate division problem FELDA settlers and their relationship with the Law and the amendment to Section Faraid 14 and 15 of Act 530 and effected to the inheritance. In addition, the effect of appointment of the Administrator issued the order under review whether the parties involved in the management of the estate is to understand or not. In addition, this study detected a conflict of the provisions of section 14 of Act 530 is the distribution of the estate was in faraid. Primary data obtained through interviews with the Small Estate Officer, Programme Manager, settlers, FELDA Management, Assistant Administrator of the Land Registry and Task-Jempol FELDA staff involved in handling cases of inheritance FELDA Settlers. Secondary data were obtained by reading text books, seminar paper, previous studies, acts, enactments, enactments, and circular and guidance in dealing with the division of property involve these settlers. Data were analyzed qualitatively and descriptively. The findings showed that the main cause of the problem division of inheritance is understand of Felda settlers at Felda Manager, Heir, heir, Small Estates Distribution Officer, Assistant Administrator of the Land and the Task-force at the FELDA scheme. Findings and proposed solutions in this study can be a catalyst for the amendment to the Act 530, Amendment of Land Act 1960 and further GSA legacy management system of FELDA settlers throughout the country..